Mars - Corrick, James A. frey50 (Franklin Watts New York, 1991)
Describes the atmosphere and surface of Mars, including recent findings from NASA space probes, and surveys the history of our attempts to discover more about this planet.
Keywords: Mars (planets) -- Juvenile literature; Mars (planets) - Exploration -- Juvenile literature; ourter space - exploration